REHYDRATION KINETICS OF MICROWAVE-DRIED BASIL - Demirhan, E.; Ozbek, B. (WILEY, 2010)
The aim of the present work was to understand the effect of drying conditions (microwave output powers and sample amounts) and rehydration temperature on rehydration kinetics of microwave-dried basil. Four different models, Peleg's, Weibull, first-order and exponential association were applied to experimental data, and the corresponding parameters of the models were obtained. Also, the kinetic parameters of the models were correlated with the ratio of microwave output power to sample amount and temperature. Although all the models applied provided a good agreement with the experimental data, the Weibull model was observed as the most appropriate one for all the experimental data, with high coefficient of determination of R-2 value. By using the kinetic parameters of this model, the activation energy for rehydration kinetic was estimated as 6.79 kJ/mol.
Keywords: WATER-ABSORPTION; DRYING KINETICS; QUALITY CHANGES; MOISTURE UPTAKE; DEHYDRATION; COWPEA; MODEL; Food Science & Technology